La dimora delle ombre: il rapporto tra Mandel’štam e Vygotskij - Luciano Mecacci (eSamizdat)
In her recent annotated edition of Mandelstam’s poems and prose, Il programma del pane. Come lievita la poesia [The Bread Program. How Poetry Rises, 2014], Lia Tosi thoroughly analyzes the relationship between Mandelstam himself and the psychologist Lev Vygotskii, two authors also linked by a strong personal friendship. Especially in the last years of his life (the early 1930s) Vygotskii was influenced by the ideas that the poet had on the genesis of the word and the structural-functional links between thinking and speech. It can be noted that the primary role assigned to verbal language, with respect to other forms of cognitive activity and practical production of the human mind, was one of the main critiques of Vygotskii from the 1930s onwards, until his ‘rehabilitation’ after the end of Stalinism.